2018
DOI: 10.1039/c8ta04697b
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen vacancy-originated highly active electrocatalysts for the oxygen evolution reaction

Abstract: Sr2VFeAsO3−δ remarkably enhances the oxygen evolution reaction by direct O–O bond formation between OH− coupled oxygen-vacant sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 43 publications
2
40
0
1
Order By: Relevance
“…In addition to the electron density distribution maps for studying the effect of charge‐transfer characteristics, the TDOS were investigated to further analyze the influence of Li + doping into NiFe LDHs on the electron‐transport process, as shown in Figure e. It was clearly demonstrated that there was a narrower band gap of Li−NiFe LDHs, in comparison with that of pristine NiFe LDHs, and thus, indicating that the Li−NiFe LDHs would have a more conductive electronic structure . Furthermore, the XPS results of valence‐band spectra have been measured (Figure S1 in the Supporting Information); the corresponding band gaps were calculated to be 0.38 and 0.85 eV for Li−NiFe LDHs and NiFe LDHs, respectively, which were in good agreement with the TDOS results.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the electron density distribution maps for studying the effect of charge‐transfer characteristics, the TDOS were investigated to further analyze the influence of Li + doping into NiFe LDHs on the electron‐transport process, as shown in Figure e. It was clearly demonstrated that there was a narrower band gap of Li−NiFe LDHs, in comparison with that of pristine NiFe LDHs, and thus, indicating that the Li−NiFe LDHs would have a more conductive electronic structure . Furthermore, the XPS results of valence‐band spectra have been measured (Figure S1 in the Supporting Information); the corresponding band gaps were calculated to be 0.38 and 0.85 eV for Li−NiFe LDHs and NiFe LDHs, respectively, which were in good agreement with the TDOS results.…”
Section: Resultsmentioning
confidence: 99%
“…Reproduced from Ref. [108] with permission from The Royal Chemical Society, Copyrights 2020 manifesting near 300 mV reduction in overpotential and 80 times higher specific activity at 1.7 V vs. RHE [116]. Chronoamperometric (CA) tests revealed that formation of oxygen vacancies in Sr 2 VFeAsO 3 − ẟ does not cause structural instabilities.…”
Section: Disadvantageous Effects Of Oxygen Vacancies In Perovskitesmentioning
confidence: 99%
“…A novel Sr 2 VFeAsO 3− δ OER electrocatalyst was designed recently, [ 99 ] the catalytic activity of which shows a dramatic enhancement at the OV of δ = 0.5. DFT calculations reveal that the OVs are initially dominated by one of the crystallographic sites (2c), while two types of crystallographic sites (2c and 4f) become fully accessible for δ > 0.5.…”
Section: Characterization Of Vacanciesmentioning
confidence: 99%